Pengembangan Media Film Bisu (Visual Gerak) pada Mata Pelajaran IPS Materi Jenis-Jenis Pekerjaan Kelas IV di SDN Cibeureum - Mohammad Fahmi Nugraha; Rika Rindayanti; Meiliana Nurfitriani (Universitas Muhammadiyah Bangka Belitung, 2020)
This research and development aims to create a learning media that is silent film (visual motion) in order to find out the quality of the media that has been developed based on assessment by media experts, material experts and assessment by 24 students on the material types of work and knowing student responses to silent media learning media (visual motion) that have been developed. The method used in the study was using the 4D model method developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. This research was conducted because there were several obstacles in class IV B of Cibeureum Elementary School during the learning process, namely the lack of students' interest in participating in social studies subjects and the lack of variations in the media used by teachers when teaching and learning activities took place. The data collection techniques and instruments in this study used test techniques, namely initial tests and final tests, and used questionnaires addressed to several experts, while the data analysis techniques in this study used descriptive statistics, namely by describing or describing collected data. Based on the research that has been done in the fourth grade of SDN Cibeureum, it can be seen that the result is an increase in the results of different tests, because it can be seen from the diagram results of the initial test and final test students get better grades with average scores the final test was 8.2 while the average score of students in the initial test was 7.5.